A comparison of the effects of RME screw height (deep Vs shallow) in maxillary constricted patients - Musa, Amro (My University, 2001)
The aim of this study is to compare the effects of rapid palatal expansion screw depth on the skeletal and dental aspects. This study involved 16 patients (7 males and 9 females); they were selected from the clinical in take of the orthodontic department in the dental faculty of Marmara University. All patients exhibited skeletal narrow maxilla and mild to moderate crowding of the maxillary dental arch. All patients were having the upper first molars and premolars present. Posterior-Anterior cephalometric films, model photocopies and models were obtained before and immediately after expansion. Nasal width was the only significant change that we had in this study (p<0.05). nasal width increased by 2.88mm in the deep screw group while in the shallow screw group it increased by only 1.00mm. thus, we found that there is no skeletal or dental effect difference between deep or shallow screw height.
Keywords: Ortodonti